High-Speed Railways in China : A Look at Traffic - Ollivier, Gerald (World Bank, Beijing, 2016)
While new transport needs are emerging and existing transport needs are growing, the network of China Railway is one of the most densely used in the world. Between 2000 and 2013, China Railways experienced robust rail traffic growth. The combination of rapidly growing traffic and of high existing traffic density called for major new investments in order for railways to continue playing a substantial role in the Chinese economy. Understanding and addressing passenger needs will be critical to achieve the full impact of the HSR network. HSR remains a major investment that requires high traffic density to be justified economically and financially. It requires careful attention to the overall door-to-door trip experience for travelers. This includes dealing with aspects that sometimes extend beyond the remit of railways, for example by improving the access to and from the station, and, in particular, reducing the current waiting time for taxis at stations or ensuring good frequency for public transport services. It also includes optimizing train frequencies and city pairing based on emerging trip patterns and user surveys, introduction flexible ticket prices reflecting peak/off-peak periods, and introducing convenient e-ticketing services. By focusing on these aspects, and on the efficient and effective operation of the HSR network, HSR in China can be expected to continue to experience substantial growth for many years to come.